Relações entre variáveis espectrais e limnológicas no reservatório da usina hidrelétrica Dona Francisca/RS - Corazza, Rosana (2010)
Continental water systems have main importance to a variety of living beings. The terrestrial remote sensing has been efficient for the study of such systems, since it allows their detailed monitoring by means of field spectroradiometers. Inserted in this context, the aim of this study was to analyze the relation between spectral variables and limnological of Dona Francisca s Hydroelectric Powerhouse reservoir, using spectroradiometry field data collection and limnology. Concerning methodology, the first stage of the study is constituted by limnological data collected in February, March, April, June, July, August and October of the year 2009, and in the obtaining of reflectance specters in October of 2009. For this aim one used 22 sample points that were defined a priori. In field and in laboratory, one determined the following limnological variables: chlorophyll-a, total suspended solids, dissolved organic carbon, Secchi disk depth, water temperature, electric conductivity and pH. The reflectance specters were acquired by field portable spectrometers FieldSpec® HandHeld. The original specters were qualitatively analyzed and one applied first order derivation technique, mapping the spectral angle, continuum removal and band reason with the aim of identifying features of absorption due to active optical components. Finally, limnological and spectral data were related by the use of correlations, dispersions and significance tests. Concerning limnological results, one found variation in the space-time distribution during the research period. The chlorophyll-a variable presented statistically significant correlations (99.9% of trust) with Secchi disk, with the total suspended solids, dissolved organic carbon and the temperature. Besides, limnological variables evidenced relationship with pluviometric precipitation regime and the consequent carrying of particled material and nutrients from the capturing bays to the hydric body. In spectral results, the maximum reflectance tax was 16% in green spectral level, approximately in 590 nm. One verified the absorption bands around 610 nm and 675 nm. According to the literature, the absorption band in 610 nm occurs because of the absorption of ficocyanine, an auxiliary photosynthetic pigment of chlorophyll-a, that is present in cyanobacterias, which indicates the existence of such organisms in the phytoplanktonic extract of the reservoir. The absorption band in 675 nm occurs due to chlorophyll-a, and it has shown to be more prominent as the pigment concentration increased. The techniques that were applied on specters made easier the interpretation and identification of the three distinct spectral groups, which were located in different sections of the reservoir: one in Jacuí River section (extreme amount), another in the Jacuizinho River section (tributary), and the other beyond the confluence of these two rivers (intermediate section until the dyke). The statistical tests evidenced that in the month of October of 2009 the reflectance was significantly statistically related to chlorophyll-a, which constituted the main optically active component that was active in Dona Francisca s reservoir water.